If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 44 = 4(4)(2) + 2(2) * H Multiply 4 * 4 44 = 16 * 2 + 2(2) * H Multiply 16 * 2 44 = 32 + 2(2) * H Multiply 2 * 2 44 = 32 + 4H Solving 44 = 32 + 4H Solving for variable 'H'. Move all terms containing H to the left, all other terms to the right. Add '-4H' to each side of the equation. 44 + -4H = 32 + 4H + -4H Combine like terms: 4H + -4H = 0 44 + -4H = 32 + 0 44 + -4H = 32 Add '-44' to each side of the equation. 44 + -44 + -4H = 32 + -44 Combine like terms: 44 + -44 = 0 0 + -4H = 32 + -44 -4H = 32 + -44 Combine like terms: 32 + -44 = -12 -4H = -12 Divide each side by '-4'. H = 3 Simplifying H = 3
| 27x+2y+7=180 | | 2a+5b-a-b= | | 81-375x^3=0 | | 24x+8=3x-9x | | 173-2x=43x+23 | | x+1.5x+.5x=234 | | 12x-278=3x-8 | | -2(8-6m+n)= | | 7-7x=25-21x | | 12x-278=3x-3 | | 29+y+x=5x | | 8-9x-5-5x=5 | | 6x-7w+2y+5w+4x+8y= | | n=20*2 | | 10x^2-10x+7=0 | | 3x^5-5x^4+17x^3=31x^2-28x+28 | | 6f+3M= | | 4v^2-28v=0 | | 2n*20= | | log(3)x+log(3)x+4=log(3)x+10 | | 4b^2-23b+15=0 | | 3x-7=44 | | 10c^2+11c-6=0 | | -4x*1x= | | -4x(x-5)= | | 20x+1=5x-6x | | 12x^2+116x-204=0 | | 8x+6x^2=15x+3x^2 | | 26-3g=8 | | (3i+2j)(7i+9j)= | | 56=-28n | | x+2=3(82-x) |